2012
DOI: 10.1007/978-94-007-4584-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Mechanisms of Oxygen Chemoreception: An Invertebrate Perspective

Abstract: Since the evolution of aerobic metabolism, cellular requirements for molecular oxygen have been the major driver for the development of sophisticated mechanisms underlying both invertebrate and vertebrate respiratory behaviour. Among the most important characteristics of respiration is its adaptability, which allows animals to maintain oxygen homeostasis over a wide range of environmental and metabolic conditions. In all animals, the respiratory behaviour is controlled by neural networks often termed respirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, we described changes in the expression of respiratory behaviour that occurred during severe hypoxia (high F B , smaller pneumostome openings), and a clear hypoxic escape‐response (i.e. migration) that has been noted for many invertebrate (Janes & Syed, ) and vertebrate taxa (Bell & Eggleston, ; Ludsin et al ., ).…”
Section: Resultsmentioning
confidence: 83%
“…In addition, we described changes in the expression of respiratory behaviour that occurred during severe hypoxia (high F B , smaller pneumostome openings), and a clear hypoxic escape‐response (i.e. migration) that has been noted for many invertebrate (Janes & Syed, ) and vertebrate taxa (Bell & Eggleston, ; Ludsin et al ., ).…”
Section: Resultsmentioning
confidence: 83%
“…The rCPG also controls cardiac functions (Benjamin and Kemenes, 2013). RPeD1 projects directly to the osphradial ganglion and receives direct excitatory, monosynaptic, cholinergic inputs from osphradial neurons (Bell et al, 2007) which are responsive to hypoxia (Janes and Syed, 2012). The parietal A group neurons innervate the musculature of the mantle cavity, while the visceral J cells are pneumostome opener motor neurones and some pneumostome closer motor neurons are thought to be located within visceral M group (Moroz, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Note that the rhythmic pattern observed in vitro mimics the respiratory cycle observed in vivo. Figure adapted and modified with permission from Syed et al, and Janes and Syed …”
Section: Identification and Reconstruction Of Simple Neuronal Circuit...mentioning
confidence: 99%
“…Using a combination of behavioral and electrophysiological approaches, we have recently reported that Lymnaea possesses a spatially distributed network of peripheral oxygen chemoreceptor sites that respond selectively to graded hypoxic challenges. 44,49 These findings suggest that the existence of multiple oxygen chemoreceptor sites is an evolutionarily conserved strategy that underlies the adaptability of respiratory behavior to meet changing environmental demands, and opens to new opportunities to investigate the fundamental synaptic mechanisms that regulate respiratory systems.…”
Section: ■ Identification and Reconstruction Of Simple Neuronal Circu...mentioning
confidence: 99%